How acceptable is adolescent self-consent for the HPV vaccination: Findings from a qualitative study in south-west England. Issue 47 (3rd November 2020) - Audrey, Suzanne; Farr, Michelle; Roderick, Marion; Evans, Karen; Fisher, Harriet
Abstract: Background: Human Papillomavirus (HPV) vaccination programmes have the potential to reduce the incidence of cervical cancer. The preferred age for HPV vaccination is 12–13 years for optimal benefit. The legal framework in England allows adolescents to be vaccinated without parental consent if they are assessed as competent. A 'South West Template Pathway on Self Consent for School Aged Immunisations' was developed to improve uptake of immunisations in south-west England. Study aim: To examine how acceptable the new procedures are to the young women, parents and carers, school staff and immunisation nurses involved. Methods: The research was undertaken in two local authorities in south-west England during the 2017/18 and 2018/19 programme years. Semi-structured digitally recorded interviews were undertaken with 53 participants: one health service manager, three immunisation nurses, five staff at alternative education providers, three staff at mainstream schools, 19 young women and 22 parents. All recordings were transcribed verbatim and thematic analysis was undertaken, assisted by NVivo software. Results: Most participants were not fully aware of the legal framework that enables a young person to self-consent to vaccination. There was a strong presumption that parents should make decisions affecting the health of their children. The preferred age at which the HPV vaccination is administered (12–13 years) contributed to reluctance in endorsing self-consent which was thought to have the potential to break down trust between parents and school staff, and within families. In practice, formal self-consent was rare. Conclusion: Unresolved issues in relation to adolescent self-consent include public and professional perceptions of young people's rights and abilities to take responsibility for decisions affecting their health, and concerns about the impact of self-consent on relationships both within families and between professionals and the families they serve.